2020
DOI: 10.1177/1129729820920103
|View full text |Cite
|
Sign up to set email alerts
|

Venous distensibility is more important than venous diameter in primary survival of autogenous radiocephalic arteriovenous fistulas

Abstract: Background: Many studies suggested that the optimal cephalic vein diameter for wrist radio-cephalic arteriovenous fistula construction should be at least 2 mm to predict successful maturation and primary patency. However, our experience has shown that many patients with smaller cephalic vein diameter (≤2 mm) in the neutral state (without a tourniquet) also have good clinical outcomes. The aim of this study was to identify predictors that affect primary survival of new wrist radio-cephalic arteriovenous fistula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Exposing the vein to this arterial environment necessarily requires physiologic vessel dilation and remodeling of the vein wall [ 16 , 17 ]. Indeed, a retrospective study by Hou et al found venous distensibility to be predictive of AVF patency and usability in patients requiring hemodialysis, even more so than the baseline venous diameter, suggesting the importance of venous adaptability [ 18 ].…”
Section: Pathophysiology Of Venous Neointimal Hyperplasiamentioning
confidence: 99%
“…Exposing the vein to this arterial environment necessarily requires physiologic vessel dilation and remodeling of the vein wall [ 16 , 17 ]. Indeed, a retrospective study by Hou et al found venous distensibility to be predictive of AVF patency and usability in patients requiring hemodialysis, even more so than the baseline venous diameter, suggesting the importance of venous adaptability [ 18 ].…”
Section: Pathophysiology Of Venous Neointimal Hyperplasiamentioning
confidence: 99%
“…According to previous studies, cephalic vein diameter of ⩽2.0 mm have high RC-AVF failure rates. 19 In our study, only two patients in the MNTT group lost patency, and the effect of venous diameter on the patency of AVF was more likely to be meaningful for patients in the conventional surgery group (control group). Large samples and long-term follow-up were needed to confirm whether the patency of AVF in MNTT cohort patients was affected by venous diameter.…”
Section: Discussionmentioning
confidence: 57%
“…Small venous diameter mean that the probability of anastomotic stenosis was higher, and it was more difficult to achieve the expected fistula diameter, flow rate and flow volume. Although the subgroup analysis indicated the tourniquet using did not influence the results, the venous distensibility played an essential role in the maturation rate of AVF, even more important than vein diameter (40). After AVFs were formed by anastomosis with arteries, the veins with good elasticity were gradually expanded under the shear stress of high-pressure arterial blood, which can quickly meet the requirements for dialysis.…”
Section: Discussionmentioning
confidence: 94%